Study of Correlation of Left Atrial Size and Atrial Fibrillation in Rheumatic Mitral Valve Disease - Shrestha, Anil; Shrestha, Richa (Journal of Nepalgunj Medical College, 2019)
Aim: To study the correlation between Atrial Fibrillation (AF) and left atrial size in Rheumatic Mitral valve disease (RMVD).Background: AF is the most common sustained cardiac arrhythmia which is associated with increased cardiovascular morbidity, mortality and preventable stroke. AF is common in rheumatic heart disease (RHD) particularly mitral stenosis (MS). LA dilatation is the predisposing factor for the development of AF in RMVD.Methodology: This is a hospital based cross sectional descriptive study conducted in 52 patients who were diagnosed as RMVD clinically and echocardiographically in NGMCTH, Kohalpur between December 2018 to November 2019. Detailed history and complete clinical examination were performed. Standard 12 lead ECG and 2-D echocardiography were done. Left atrial size was measured and compared with patients in AF and with sinus rhythm.Result: The age of patients ranged from 20-76 years with the mean age of 40.33 years. Out of 52 patients 30 were in AF and 23 in sinus rhythm. Among 30 patients in AF, 27 (90%) had LA size ≥ 4 cm with mean LA size of 4.6 cm whereas among 22 patients in sinus rhythm, 14 (63.64%) had LA Size